Peningkatan Hasil Belajar Bahasa Inggris pada Materi Degree osf Comparison Melalui Penerapan Model Pembelajaran Problem Based Learning - Rapidli, Rapidli; La Sunra, La Sunra; Hasyim, Hasyim (Indonesian Journal of Pedagogical and Social Sciences, 2023)
Abstract. This study aims to improve the English learning outcomes of class VIII E students of SMP Negeri 2 Sinjai through the Problem Based Learning model. This type of research was Classroom Action Research which was conducted from April to June 2023. The number of research subjects was 29 people consisting of 14 men and 15 women. The research procedure consisted of two cycles. The research data is qualitative data obtained by using question sheets, observation sheets, and documentation. Data is processed using descriptive qualitative. The factors studied were student factors, process factors, and learning outcomes factors. The results of the study show an increase in learning outcomes, this is based on the presentation of student learning outcomes. The learning outcomes of students at the pre-cycle stage were 20.68% of students who completed. In the first cycle there was an increase to 44.82% of students who passed, while for the second cycle there was a significant increase, namely 79.32 students who passed. So it can be concluded that the application of the Problem Based Learning model can improve the learning outcomes of class VIII E students of SMP Negeri 2 Sinjai. Keywords: Problem Based Learning, Degree of Comparison, Learning Outcomes